Controlling the rate of change of Ni dispersion in commercial catalyst by ALD overcoat during dry reforming of methane. (28th April 2020) - Afzal, Shaik; Prakash, Anuj V.; Littlewood, Patrick; Marks, Tobin J.; Weitz, Eric; Stair, Peter C.; Elbashir, Nimir O.
Abstract: This study investigates changes in dispersion with time-on-stream of a Ni catalyst coated with alumina by Atomic Layer Deposition (ALD) in Dry Reforming of Methane (DRM) conditions. A 20 wt% commercial Ni catalyst is coated with 5, 10, and 20 ALD cycles and tested for DRM at 650 °C, 1 atm for 40 h. Using an in-situ H2 –CO pulse chemisorption technique, it is found that the rate of decline in catalyst dispersion is more rapid in the uncoated catalyst ( 0.11%h −1 ) than 5-ALD catalyst ( 0.025%h −1 ). TEM images before and after reaction show that the average particle size for the uncoated catalyst increases from 8.5 nm to 24.5 nm, indicating sintering, whereas the 5-ALD catalyst retained the initial particle size. The reduced particle size also explains the 50% reduction in carbon formation-rate in the 5-ALD catalyst. The developed sequential H2 –CO chemisorption technique reliably measures in-situ dispersion in uncoated and ALD coated catalysts with exposed active sites. Graphical abstract: Image 1 Highlights: A dual H2 –CO chemisorption method for in-situ estimation of catalyst metal dispersion. Rate of dispersion loss much lower in ALD-coated Ni catalysts than uncoated catalyst. Chemisorption results contrasted with TEM. Unusual CO adsorption and H2 desorption patterns for ALD catalysts.